PHLDA1 Mediates Drug Resistance in Receptor Tyrosine Kinase-Driven Cancer - Abbie E. Fearon; Edward P. Carter; Natasha S. Clayton; Edmund H. Wilkes; Ann-Marie Baker; Ekaterina Kapitonova; Bakhouche A. Bakhouche; Yasmine Tanner; Jun Wang; Emanuela Gadaleta; Claude Chelala; Kate M. Moore; et al. (Cell Reports, 2018)
Summary: Development of resistance causes failure of drugs targeting receptor tyrosine kinase (RTK) networks and represents a critical challenge for precision medicine. Here, we show that PHLDA1 downregulation is critical to acquisition and maintenance of drug resistance in RTK-driven cancer. Using fibroblast growth factor receptor (FGFR) inhibition in endometrial cancer cells, we identify an Akt-driven compensatory mechanism underpinned by downregulation of PHLDA1. We demonstrate broad clinical relevance of our findings, showing that PHLDA1 downregulation also occurs in response to RTK-targeted therapy in breast and renal cancer patients, as well as following trastuzumab treatment in HER2+ breast cancer cells. Crucially, knockdown of PHLDA1 alone was sufficient to confer de novo resistance to RTK inhibitors and induction of PHLDA1 expression re-sensitized drug-resistant cancer cells to targeted therapies, identifying PHLDA1 as a biomarker for drug response and highlighting the potential of PHLDA1 reactivation as a means of circumventing drug resistance. : Fearon et al. use unbiased transcriptomic and phosphoproteomic analysis to identify PHLDA1 as a mediator of acquired resistance to kinase-targeted therapies in cancer. Using a range of cell models and clinical data, they uncover a mechanism underpinning the re-wiring of Akt signaling in cancer drug resistance. Keywords: tyrosine kinase inhibitor, drug resistance, FGF, Akt, targeted therapy, cancer